ANALYSIS OF SOURCES ON HANAFI JURISPRUDENCE IN THE 18TH-19TH CENTURIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This study provides a comprehensive examination of the sources and intellectual transformations that shaped Hanafi jurisprudence during the 18th and 19th centuries. In this period, Muslim legal scholars and institutions encountered profound socio-political shifts, particularly due to colonial encroachment, legal reforms, and educational changes across regions such as South Asia, Central Asia, and the Ottoman Empire. The research explores how traditional Hanafi legal frameworks responded to these challenges through a renewed emphasis on ijtihad (independent reasoning) and reinterpretation of classical texts. Central figures such as Ibn Khaldun and Shah Waliullah Dehlawi contributed significantly to the evolution of Islamic legal thought, offering methodological tools for adapting jurisprudence to emerging realities. The paper also analyzes the intersection between religious and secular authority, the influence of madrasas, and the integration of customary law with formal legal institutions. By engaging with both primary texts and contemporary scholarly interpretations, this study highlights the dynamic adaptability of Hanafi jurisprudence and its enduring relevance in confronting modern legal, ethical, and epistemological issues.